Non-mental diseases associated with ADHD across the lifespan: Fidgety Philipp and Pippi Longstocking at risk of multimorbidity?. (January 2022) - Kittel-Schneider, Sarah; Arteaga-Henriquez, Gara; Vasquez, Alejandro Arias; Asherson, Phil; Banaschewski, Tobias; Brikell, Isabell; Buitelaar, Jan; Cormand, Bru; Faraone, Stephen V.; Freitag, Christine M.; Ginsberg, Ylva; Haavik, Jan; et al.
Highlights: Non-mental diseases over the lifespan are associated with ADHD. Epilepsy, migraine, elimination disorders, asthma and obesity are significantly associated with ADHD over the lifespan. Diagnosing non-mental diseases in ADHD patients is important for optimizing the treatment of both conditions. Abstract: Several non-mental diseases seem to be associated with an increased risk of ADHD and ADHD seems to be associated with increased risk for non-mental diseases. The underlying trajectories leading to such brain-body co-occurrences are often unclear - are there direct causal relationships from one disorder to the other, or does the sharing of genetic and/or environmental risk factors lead to their occurring together more frequently or both? Our goal with this narrative review was to provide a conceptual synthesis of the associations between ADHD and non-mental disease across the lifespan. We discuss potential shared pathologic mechanisms, genetic background and treatments in co-occurring diseases. For those co-occurrences for which published studies with sufficient sample sizes exist, meta-analyses have been published by others and we discuss those in detail. We conclude that non-mental diseases are common in ADHD and vice versa and add to the disease burden of the patient across the lifespan. Insufficient attention to such co-occurring conditions may result in missed diagnoses and suboptimal treatment in the affected individuals.